2011
DOI: 10.1111/j.1743-6109.2009.01645.x
|View full text |Cite
|
Sign up to set email alerts
|

Abortions and Contraception Use Among Czech and Romanian Women: Comparison of Representative National Studies

Abstract: Introduction This article presents the results of representative national studies comparing the behavior and attitudes of Czech and Romanian women regarding abortion and contraception use. Aim Describe the attitudes to abortion and incidence of abortion in female population of these countries. Methods Independently and anonymously conducted questionnaire with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The main factors in choosing contraception in Romania are safety and simplicity. In the Czech Republic, the main factors are reliability, contentment, and convenience [17]. A study done to see contraceptive prevalence in southeast Asia suggests that in Bangladesh (58%) it was similar to India (56%) and, somewhat lower in Nepal (48%) [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factors in choosing contraception in Romania are safety and simplicity. In the Czech Republic, the main factors are reliability, contentment, and convenience [17]. A study done to see contraceptive prevalence in southeast Asia suggests that in Bangladesh (58%) it was similar to India (56%) and, somewhat lower in Nepal (48%) [18].…”
Section: Discussionmentioning
confidence: 99%
“…The research regarding contraceptive usage, knowledge, and practices in other developing countries has also shown that there was a wide gap between knowledge and contraceptive use [15–17]. The contraceptive prevalence in Pakistan was 47%, the most common method used was barrier method; sterilization (2%) was the least common [15].…”
Section: Discussionmentioning
confidence: 99%
“…If prenatal screening identifies a congenital malformation, the respondents considered the physician to have a duty to recommend therapeutic abortion. Again, this shows a good moral compass -the permissibility of prenatal screening without giving the option to safely perform the abortion may lead for the affected women to chose between giving birth to a child with a severe adaptation deficit, or perform the abortion in non-safe environments, a true medical hazard (27)(28)(29)(30)(31). The item regarding the right to reproduction of psychiatric patients and those with severely diminished mental capacity was inserted to test the mimesis of the respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Campaigns for information and education in regard to contraceptive methods, as well as greater involvement of the institutions in order to improve education and accessibility, in terms of sexuality and contraception, are still necessary [38,39].…”
Section: Discussionmentioning
confidence: 99%